Pharmaceutical Use and Expenditure for Cardiovascular Disease and Stroke A Study of 12 OECD Countries - Dickson, Michael (OECD Publishing, 2003)
This study presents the results of a joint analysis of patterns of consumption, expenditure, and unit expenditure for a core set of drugs aimed at preventing and treating cardiovascular disease. The current study examines the relationships among three pharmaceutical variables (expenditure, volume of drug use, and unit expenditure) classified according to eight therapeutic categories which are specific for the prevention and treatment of cardiovascular disease and stroke. It covers an 11-year time period, and specifies relevant country-specific structural features in a sample of 12 OECD countries. The data presented in this report show how the three descriptive pharmaceutical variables vary across these countries. The study also contains a preliminary exploration of factors associated with variation in these variables across countries and through time. Findings for each of the eight cardiovascular disease and stroke drug therapeutic categories investigated in this study are ...
Keywords: Social Issues/Migration/Health